Social Network Research in Organizational Contexts: A Systematic Review of Methodological Issues and Choices - Carpenter, Mason A.; Li, Mingxiang; Jiang, Han (Journal of management, 2012)
A large body of research has examined social networks in organizational contexts. While this work has enhanced scholars’ understanding of the antecedents and consequences of networks, missing from this literature is a comprehensive framework that simplifies and clarifies this complex body of work. In response, the authors develop a framework that classifies network research into four major categories, with the purpose of guiding scholars’ choices among the various theories, constructs, measures, research designs, and analytic strategies inherent in the social network literature. The authors also provide recommendations for future work aimed at advancing the state of network research in organizational contexts.